Inhibition of pancreatic cholesterol esterase reduces cholesterol absorption in the hamster - Heidrich, John E (BioMed Central, 2004)
BACKGROUND: Pancreatic cholesterol esterase has three proposed functions in the intestine: 1) to control the bioavailability of cholesterol from dietary cholesterol esters; 2) to contribute to incorporation of cholesterol into mixed micelles; and 3) to aid in transport of free cholesterol to the enterocyte. Inhibitors of cholesterol esterase are anticipated to limit the absorption of dietary cholesterol. RESULTS: The selective and potent cholesterol esterase inhibitor 6-chloro-3-(1-ethyl-2-cyclohexyl)-2-pyrone (figure 1, structure 1) was administered to hamsters fed a high cholesterol diet supplemented with radiolabeled cholesterol ester. Hamsters were gavage fed (3)H-labeled cholesteryl oleate along with inhibitor 1, 0–200 micromoles. Twenty-four hours later, hepatic and serum radioactive cholesterol levels were determined. The ED(50 )of inhibitor 1 for prevention of the uptake of labeled cholesterol derived from hydrolysis of labeled cholesteryl oleate was 100 micromoles. The toxicity of inhibitor 1 was investigated in a 30 day feeding trial. Inhibitor 1, 100 micromoles or 200 micromoles per day, was added to chow supplemented with 1% cholesterol and 0.5% cholic acid. Clinical chemistry urinalysis and tissue histopathology were obtained. No toxicity differences were noted between control and inhibitor supplemented groups. CONCLUSIONS: Inhibitors of cholesterol esterase may be useful therapeutics for limiting cholesterol absorption.